Spectroscopic studies of chlorophyll a from Opuntia ficus-indica - Rusli, M.S.; Abidin, Z.H.Z.; Taha, R.M.; Arof, Abdul Kariem (Springer Verlag (Germany), 2009)
Green pigment obtained from Opuntia ficus-indica intact plant was solvent extracted with absolute ethanol. The pigment solution was subjected to various photoexcitations at wavelengths of 222, 308, 337 and 448 nm. Fluorescence from the excited state exhibit peaked in the regions 450-485 nm and 650-680 nm. Upon comparison with the literature, the green solution is chlorophyll a. Fluorescence intensity ratio ( blue to red) differs with excitation wavelengths. It is known that chlorophyll a fluoresces at 673 nm. From the absorption spectrum, the peaks at similar to 404, similar to 501, similar to 605 and similar to 663 nm correspond to the singlet 4 (S4), singlet 3 (S3), singlet 2 (S2), and singlet 1 (S1) peaks, respectively.